PENGARUH PEMBIASAAN PENDIDIKAN AGAMA PADA ANAK TERHADAP LINGKUNGAN MASYARAKAT DI DESA BUNGBULANG - Ependi, Pendi Khoer; Rofiah, Evi Siti (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
Habit is an educational process that takes place by accustomingchildren to behaving, speaking, thinking and carrying out certainactivities according to good habits. Habit has an effect on theindividual, if he is used to doing things or behavior well then he will getused to doing it and vice versa if he is accustomed to doing badbehavior then he will get used to it too. But in this case enlightenmentor education needs to accompany the habituation so that it becomesstronger and stronger.So, giving religious education to children is veryimportant. That will affectcharacter and personality of the child for the future. And it is also moreuseful especially in the community